MENGATASI STRESS DENGAN HIPNOTERAPI BAGI KORBAN PERSELINGKUHAN - Rahmaditta Kurniawati; ZULKIPLI LESSY; Arif Widodo (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2022)
Affair by one partner will have a negative impact on the family. A wife who finds her husband cheating on her will be prone to stress. Stress that is not immediately handled in cases of infidelity will increase to depression and psychosomatic. In Karanganyar there is a Ztrongmind Institute that offers Hypnotherapy practices in dealing with stress and psychosomatics. The purpose of this research; First, to find out the process of implementing the hipnotherapy method in dealing with stressful clients due to infidelity at the Ztrongmind Karanganyar Institute. Second, to find out the impact felt by the client on the therapy process he underwent at the Ztrongmind Karanganyar Institute. The method in this study uses a qualitative approach with the subject of three clients in Zstrongmind who experience stress due to being cheated on by their partners. The results of this study found that Ztrongmind has therapeutic intervention that is unique to Ztrongmind, namely the quantum technique Meanwhile, clients who participated in a full hypnotherapy session said that they experienced a reduction in stress.